The Influence Of Service Quality, Facilities And Marine Safety On Customer Satisfaction KM Kelud PT Pelni - Ghozi, Fahmi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
Sea transportation plays a pivotal role in Indonesia's economic growth and national integration. PT Pelayaran Nasional Indonesia (PELNI) is responsible for providing maritime transportation services to various regions throughout the country. As a public service enterprise, PELNI is dedicated to ensuring the provision of reliable and affordable sea transportation services. Furthermore, economic shifts have an impact on PELNI, necessitating a competitive stance and the ability to navigate the current competitive landscape. This study aims to analyze the effect of service quality, facilities, and shipping safety on passenger satisfaction on KM Kelud in PT PELNI sea transportation. The study employs a descriptive quantitative research method with a population of passengers on the KM Kelud PT PELNI ship, comprising a total of 3,865 individuals, with a sample size of 100 respondents. The data collection technique employs a questionnaire that has been validated for reliability and tested for validity. The analytical tool used is SEM PLS 4.0 (Structural Equation Model - Partial Least Square). The findings indicated that service quality, facilities, and shipping safety had a favorable impact on passenger satisfaction on the KM Kelud.